Retinal organoids and microfluidic chip-based approaches to explore the retinitis pigmentosa with USH2A mutations - Su, Ting; Liang, Liying; Zhang, Lan; Wang, Jianing; Chen, Luyin; Su, Caiying; Cao, Jixing; Yu, Quan; Deng, Shuai; Chan, Hon Fai; Tang, Shibo; Guo, Yonglong; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Retinitis pigmentosa (RP) is a leading cause of vision impairment and blindness worldwide, with limited medical treatment options. USH2A mutations are one of the most common causes of non-syndromic RP. In this study, we developed retinal organoids (ROs) and retinal pigment epithelium (RPE) cells from induced pluripotent stem cells (iPSCs) of RP patient to establish a sustainable in vitro RP disease model. RT-qPCR, western blot, and immunofluorescent staining assessments showed that USH2A mutations induced apoptosis of iPSCs and ROs, and deficiency of the extracellular matrix (ECM) components. Transcriptomics and proteomics findings suggested that abnormal ECM-receptor interactions could result in apoptosis of ROs with USH2A mutations via the PI3K-Akt pathway. To optimize the culture conditions of ROs, we fabricated a microfluidic chip to co-culture the ROs with RPE cells. Our results showed that this perfusion system could efficiently improve the survival rate of ROs. Further, ECM components such as laminin and collagen IV of ROs in the RP group were upregulated compared with those maintained in static culture. These findings illustrate the potential of microfluidic chip combined with ROs technology in disease modelling for RP.